STRATEGI PENGEMBANGAN CITRA MEREK DI SMA KHALIFA IMS KOTA TANGERANG SELATAN - Maharsiwi Diah Chandra Dewi; I Made Sukresna (ITB AAS Indonesia Surakarta, 2023)
This research is a qualitative research. Data collection was carried out by interview method. Respondents were parents, teachers, principals, school committee and main director of SMA Khalifa IMS, South Tangerang City. Seeing the increasingly fierce competition in the world of education, managers of educational institutions are getting stronger to continue to compete in improving the quality of education. SMA Khalifah IMS is a newly established school and currently the school needs a lot of promotion in order to get a good brand image. In this study, respondents were asked about their perceptions of the school's brand image. The results of the interviews obtained an overview of the students' parents assessing the quality of the IMS Khalifah school both for kindergarten, elementary and junior high schools. But it needs proof for the high school level, the quality in question is the integration of the Cambridge and Islamic curricula. In addition, there are several negative brand images that are felt by parents of students, including school facilities that are still lacking, especially buildings, sports fields and parking lots, there are several teachers who are less professional in mastering English. On the other hand, the school has made various efforts to improve the school's brand image through improving the quality of teachers, adding school facilities, marketing activities, providing scholarships, organizing events and competitions. The increased brand image is expected to increase the interest of parents to entrust their children to attend Khalifa IMS High School. Keywords: brand image, high school, marketing, promotion